Lower Lip Pits: Van der Woude or Kabuki Syndrome?. (November 2014) - David-Paloyo, Ferri P.; Yang, Xuecai; Lin, Ju-Li; Wong, Fen-Hwa; Wu-Chou, Yah-Huei; Lo, Lun-Jou
Kabuki syndrome (KS) is a multiple congenital anomaly/mental retardation syndrome with characteristic facial features. Despite more than 350 documented cases and recent correlation of MLL2 mutations as a genetic cause, its full clinical spectrum is still being defined. This report describes two patients who were initially diagnosed with Van der Woude syndrome (VWS) based on the presence of lower lip pits. However, this finding can occur with KS, albeit infrequently. For patients with lower lip pits, a thorough evaluation should be made to distinguish between VWS and KS, as there are differences in long-term prognosis.